Lexicography of Paroemias: The Problem of Interpretation (Based on the Russian Language) - Olga N. Ivanishcheva (Вестник Северного (Арктического) федерального университета: Серия «Гуманитарные и социальные науки»)
The article describes the methods of interpreting paroemias in modern phraseological and proverb dictionaries. The paper aims to identify the principles of such interpretation. It is known that determining the meaning of a paroemia, which is presented in most phraseological and proverb dictionaries of the modern Russian language, is not enough for the correct use of the phraseological unit or proverb in speech practice. However, the question of selecting such information for dictionaries and its systematization has not yet been raised in scientific literature. The article studies the following methods of interpreting paroemias: determining their direct (if any) and figurative meanings, historical and etymological commentary, as well as situational and contextual characterization. As a result, it was established that historical and etymological commentary in the definitions of modern dictionaries explains the origin of a paroemia, taking into account regional specifics. Situational characterization is defined here as a description of a situation with the identification of its participants and their social and speech intentions, while contextual characterization is understood as the content of a formulaic reply to the interlocutor’s question. It is argued that determining a hierarchy of methods for interpreting paroemias accomplishes the main task, i.e. the actualization of the image underlying a paroemia and the presentation of this image in a dictionary. The theoretical significance of the paper lies in its contribution to the theory and practice of lexicography. In practical terms, the results can be used when compiling dictionaries of phraseological units and proverbs of different languages, including those with different structures, as well as when teaching Russian as a first and second/foreign language.